Hooray! My butt left the bench! - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Here's Hank, 2017)
Hank will need help from his father and friends if he is to help his second grade basketball team beat their arch rivals for the third year in a row.